How to be a better tourist : tips for a truly rewarding vacation - Idema, Johan, ....- (Amsterdam : BIS, 2018)
Why do we descend en masse on the same cities, cluster around the same attractions and all visit the same picturesque neighborhoods that can't actually handle the influx? How to Be a Better Tourist takes a fresh look at making your vacation truly worthwhile, gaining a genuinely rewarding experience. Vacations are made of freedom. Pure freedom. Our busy lives, full of obligations, mean that vacations may be the only times we can do whatever we want, wherever we want. So just how weird is it that we all spend that precious time doing the same things? That we descend en masse on the same cities, cluster around the same attractions and all visit the same picturesque neighborhoods that can't actually handle the influx? How to be a Better Tourist takes a fresh look at making your vacation truly worthwhile. After all, what if all your vacations seem to be getting more and more the same? What if being a tourist is suddenly no longer quite as innocent as it first seemed? Or what if your long list of must-sees, in fact, stresses you out? As the writer, Elbert Hubbard poignantly put it, “No man needs a vacation so much as the man who has just had one.” Find out why you should perhaps stay at home. Understand why you also need to work while on vacation. Read why tourists should visit supermarkets and residential districts too. Our typical vacation behavior – visiting the maximum number of highlights in the minimum time – is rarely the most rewarding. How to be a Better Tourist helps you get the most out of your stay without damaging the soul of your destination. Because, ultimately, an imaginatively considered vacation is a genuinely rewarding experience. Johan Idema is a passionate promoter of innovation in the art world. He likes innovative vacations too.
Keywords: Tourism